Primary patency of native arteriovenous fistula in elderly at Abdul Wahab Sjahranie Hospital, Samarinda, Indonesia - Muhammad Rizki Bachtiar; Ivan Joalsen; Izzati Nurmaya Sari; Made Angga Putra (Journal of Indonesia Vascular Access, 2021)
Introduction. Arteriovenous fistula (AVF) is preferred to be selected by the patient and clinician due to long term survival and fewer complications than other vascular access. Radiocephalic (RC) fistula is the first choice for dialysis access and should be performed in elderly renal failure patients. Several authors have advocated that the brachiocephalic (BC) fistula should be considered the surgeons' first option. We aim to analyze the primary patency of RC and BC AVF in the elderly. Method. This prospective cohort study was conducted from June 2018 to March 2020, which included 58 elderly patients who underwent surgery to create AVF. Demographic data were collected from medical records. Meanwhile, information about patient’s primary patency of RC and BC AVF were followed up to first access dysfunction or any intervention by phone. The survival data were analyzed using the Kaplan-Meier method Result. There were 58 elderly patients divided into 51 (87.9 %) patients with RC, 4 (6.9%) patients with BC, and 3 (5.2%) patients with Basilic Vein Transposition (BVT). The survival rate of RC was 70.5 % after six months and 29.4 % after 12 months. Meanwhile, 50% of BC patients survived in the first six months, and 25% survive for a year. On the other hand, 1 of 3 patients died in the BVT group in the first month after access placement due to hemodialysis complication, and the remaining two BVT patients survived in three months. Conclusion. RC has a patency rate of 70.5% in six months and 29.4% in a year. Choosing the right type and site of the anastomosis is essential as life expectancy increases in the elderly to preserve the veins for future access site.